Influence Political Law in Formation and Enforcement Law in Indonesia - Rudi Salam Tarigan; Ismaidar Ismaidar; Tamaulina Br. Sembiring (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Indonesia continues to face complex political and legal challenges. The developing political dynamics are a factor that influences the implementation of legal policies based on the principles of justice and the needs of the community. Efforts to improve law enforcement are carried out by accommodating the aspirations of the community, increasing the professionalism of law enforcement officials, and legal institutions. Legal politics is an activity to monitor law enforcement to achieve the goals of the state that has been set. This research aims to discuss the role of legal politics in the formation and enforcement of law in Indonesia. This study uses secondary data, obtained from the literature of journals on legal politics. Conclusion: the implementation of legal policies is sometimes still influenced by the interests of political elites, who use their power to enforce the law. However, this can be prevented by increasing public awareness to monitor law enforcement based on Pancasila values actively.